Study of saline effects in Azospirillum spp isolated from agricultural soils : south of Thi Qar governorate - Hasanain Ali Al-Kinani, Hasanain Ali Al-Kinani (University of Thi-Qar Journal of agricultural research, 2024)
Biofertilizers, containing microorganisms, colonize plant roots or interiors, increasing nutrient supply and stimulating growth. High salinity in agricultural soils reduces water absorption, growth rate, and photosynthetic activity, leading to physiological dehydration and growth inhibition. To develop biofertilizers, Azospirillum spp isolates were used, which are symbiotic nitrogen-fixing bacteria that promote plant growth, absorb minerals, and absorb water. The study aimed the impact of varying NaCl concentrations on the growth and effectiveness of Azospirillum spp isolates from five agricultural areas in the Fadliya district south of Thi Qar governorate. The isolates, all Gram-negative, were motile and responded to the requirements of biotin and pectin did not decompose during this study, except for the AZOST.3 isolate, they did not need decomposed biotin and pectin. The results of the current study showed the growth of Azospirillum spp at various levels of NaCl at a field capacity of 28% . All isolates recorded good growth at a minimum concentration of 3% NaCl, and growth gradually decreases with increasing salt concentration until reaching a concentration of 5% NaCl, which shows the extent of the portability of these isolates to grow at high concentrations of salt and its interference with humidity within the field capacity of 28%, as these isolates recorded more growth and tolerability of high salt concentrations compared to the low growth recorded by the AZO ST.1, AZO ST.2, and AZO ST.3 through a concentration of 4% NaCl at a field capacity of 14% .The study of the growth of Azospirillum spp at different pH levels also showed a variation in the growth intensity within the isolated strains of Azospirillum, as all five isolates recorded a gradual growth from the lowest level at pH 5.5 to pH 8.5 . It was also found that they can grow at high pH levels, which proves their potential as successful vaccines for cultivation in saline and alkaline soils.